The first influenza pandemic of the new millennium - Neumann, Gabriele (Blackwell Publishing Ltd, 2011)
Please cite this paper as: Neumann G, Kawaoka Y. (2011) The first influenza pandemic of the new millennium. Influenza and Other Respiratory Viruses DOI: 10.1111/j.1750‐2659.2011.00202.x. In the spring of 2009, a novel influenza A virus of the H1N1 subtype emerged that transmitted efficiently among humans; by June of 2009, the outbreak reached pandemic status. The pandemic virus possesses six viral RNA segments from so‐called triple reassortant swine viruses that emerged in North American pig populations in the late 1990s and two viral RNA segments from Eurasian avian‐like swine influenza viruses. Most human infections with the virus have been mild; however, severe and fatal infections occurred among certain risk groups, but also among those without any known risk factors. Here, we summarize the evolutionary, epidemiological, clinical, and molecular findings on the pandemic virus. We also discuss the arsenal of antiviral compounds and vaccines available to prevent and treat infections with the virus.